PENGARUH HARGA DAN KUALITAS PELAYANAN SERTA KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PADA BAKSO PAK MIAD KECAMATAN TAMAN KABUPATEN PEMALANG - Dani Agung Wicaksono; Trias Ayu Laksanawati; Dwi Budian Ningsih (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2021)
The meatball stall which is a typical dish from Pemalang is Pak Miad's meatball. Pak Miad's meatball stall is the pioneer of meatball traders in Pemalang because it has been established since 1967. Pak Miad's meatball stall is famous for its different shape from meatballs in general. The purpose of this study was to determine the effect of price and service quality and product quality on consumer satisfaction at Pak Miad's meatballs in Taman Subdistrict, Pemalang Regency by proposing five hypotheses. Quantitative research used in this research. The sample obtained was 100 respondents using purposive sampling technique using Multiple Linear Regression data analysis which included validity and reliability tests, classical assumption test, multiple linear regression analysis, testing through t test and F test, and coefficient of determination (R2) test. The results showed that the service quality variable had no significant effect on customer satisfaction. Product quality variable has a significant effect on consumer satisfaction and product quality is the variable that has the most dominant influence on consumer satisfaction